Mama built a little nest - Ward, Jennifer (Beach Lane Books, 2014)
Illustrations and simple, rhyming text introduce different kinds of birds' nests, from the scrapes falcons build on high, craggy ledges to the underground nests burrowing owls dig. Includes brief facts about each kind of bird
Auch als E-Book erhältlich
Keywords: Birds -- Nests -- Juvenile literature; Birds -- Juvenile literature; Vögel; Brutbiologie; Nestbau; Sachbilderbuch